The Adoption Of MOOC Utilization Among Undergraduate Students In Universiti Teknikal Malaysia Melaka (UTeM) - Al-Shami, Samer Ali Hussein; Aziz, H.; Abd. Rashid, Nurulizwa (J Fundam Appl Sci., 2018)
In the present worldwide age,web based learning has turned out to be one of the principle of education.A couple of years’ prior have seen the (MOOC) as learning patterns in the field motivation in the establishments as it is tended to in the Eleventh Malaysian Plan (2016-2020),the National Economic Model,Economic Transformation Program and the Malaysian Education Plan which expected for advanced education.Be that as it may,its clients remind low and have not yet achieved the guarantee number.This softened an inquiry up how to persuade understudies to utilize MOOCs in their instruction procedure.Consequently,this paper researches the progression that influence MOOC usage among college understudies at Universiti Teknikal Malaysia Melaka (UTeM).